The Eastward Enlargement of the Eurozone Trade and FDI - José Manuel Martins Caétano; Aurora Galego; Elsa Cristina Vaz; Carlos Vieira; Isabel Vieira (Free University Berlin, Jean Monnet Centre of Excellence, 2002)
The objective of this study is to examine recent developments in trade and FDI flows between the EU and the CEEC, trying to anticipate future consequences from the economic integration of the two blocks. Economic theory suggests that integration conveys positive effects upon welfare, due to the reallocation of resources and the restructuring of production and trade. The Eastern enlargement represents both an opportunity and a risk for the EU members as well as for the CEEC. As a result of the differences in size between the two groups of countries involved, it is likely that on average the CEEC will face the highest risks but may also experience the largest benefits. It is expected that both trade and FDI flows will increase with deeper economic integration. However, the free circulation of goods, services and capital over a wider geographic area creates opportunities for the exploitation of scale economies, which may lead to the geographical concentration of production. Therefore, in spite of the expected positive global effects, it is acknowledged that, during the transition period, difficulties may arise in those sectors, regions and firms confronted with new competitive challenges. In the CEEC, transition from centrally planned to market economies coexists with the plans for future integration in the EU. Both processes prompt internal and external liberalisation processes, with social and economic consequences that are difficult to predict. In order to develop a coherent study in such a complex context, an attempt is made to integrate different analytical perspectives. The exhaustive assessment of the changes in the pattern of trade between candidates and current EU members comprehends an analysis of the global intensity of trade flows and of potential trade creation and diversion effects. The study also examines tendencies for sectoral specialisation and the evolution of the position of countries in the process of international segmentation of production. In respect to FDI, an empirical assessment of its main determinants is followed by the evaluation of potential diversion of investment flows from the EU periphery to the CEEC.
Keywords: F17; F15; 330; Trade and FDI; Economic Integration; EU-Erweiterung; Europäische Wirtschafts- und Währungsunion; Aussenwirtschaft; Internationale Arbeitsteilung; Intraindustrieller Handel; Direktinvestition; Schätzung; Osteuropa; EU-Staaten